The Role of Cultural Capital on the Performance of Agricultural and Industrial Cooperatives of Boyerahmad Township - A. Mirfardi; S. Ahmadi; A. Sadeqnia; M. J. Rostami (تعاون و کشاورزی, 2015)
Abstract The main purpose this study was to investigate the cultural capital and demographic characteristics on the Performance of Agricultural and Industrial Cooperatives of Boyerahmad Township. Using survey and documentary methods, statistical population included 210 members of Agricultural and Industrial Cooperatives of Boyerahmad Township, from which 136 members were selected as sample size based on Morgan sampling Table and selected via approporiate multistage random sampling. Findings showed that "cultural behaviors and procedures" and cultural capital had linear relationship with the dependent variable, but there was no relationship between the kind of cultural goods consumption and the dependent variable. "Cultural behaviors and procedures" and cultural capital, totally, had explained 33.6 percentages of the dependent variable variance. There was no significant difference between the dependent variable according to the demographic variables (such as gender, marital situation, and education, membership and activity history of members).